Quality assurance in ophthalmic imaging - Dubey, Suneeta (Indian J Ophthalmol, 2019)
Quality assurance (QA) is the maintenance of a desired level of quality in a service, by means of attention to every stage of process of delivery. Correct image acquisition along with accurate and reproducible quantification of ophthalmic imaging is crucial for evaluating disease progression/stabilization, response to therapy, and planning proper management of these cases. QA includes development of standard operating procedures for the collection of data for ophthalmic imaging, proper functioning of the ophthalmic imaging equipment, and intensive training of technicians/doctors for the same. QA can be obtained during ophthalmic imaging by not only calibration and setting up of the instrument as per the manufacturer's specifications but also giving proper instructions to the patients in a language which they understand and by acquisition of good quality images. This review article will highlight on how to achieve QA in imaging which is commonly being used in ophthalmic practice.